Stingless bee honey as functional food - A review - Tan, Fuen Ann T; Ho, Ai Ling; Fook, Yee Chye (UniSE Press, 2024)
Stingless bee honey (SBH) is one of the high value products that have been marketed worldwide. Honey contains unique and distinct compounds of variable nutritional and biological importance. As a natural product harvested from stingless bees, it is rich in bioactive compounds, antioxidants, sugars, amino acids, minerals and vitamins. This review discusses the physicochemical characteristics, nutritional composition, bioactive compounds and functional properties of SBH which contribute to human health. Prospects of SBH are discussed in association to its sustainability and feasibility as a functional food to meet the demands of consumer. It is important that SBH is developed into a sustainable product, providing additional income opportunities for local farmers while ensuring consumer safety and product quality.